2012
DOI: 10.1590/s0100-40422012000500015
|View full text |Cite
|
Sign up to set email alerts
|

Desreplicação de alcaloides aporfínicos e oxoaporfínicos de Unonopsis guatterioides por ESI-IT-MS

Abstract: Recebido em 14/7/11; aceito em 25/11/11; publicado na web em 20/1/12 DEREPLICATION OF APORPHINE AND OXOAPORPHINE ALKALOIDS FROM Unonopsis guatterioides BY ESI-IT-MS. The dereplication of aporphine and oxoaporphine alkaloids by direct infusion in ESI-IT-MS n system was applied for alkaloidal fractions of the Unonopsis guatterioides (Annonaceae). Its main advantage over other dereplication methods is the ability to quickly identify substances in complex mixtures without the use of coupled techniques and expensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The alkaloid fraction from the barks of the trunk of U. guatterioides, (IC50 2.79 μg/mL) also showed significant activity, that can be attributed to the oxaporphine alkaloids liriodenina (3) and lisycamine (4) (Silva et al, 2012a), which showed good leishmanicidal activity (Waechter et al, 1999) when evaluated against promastigotes form of L. major and L. donovani. Liriodenine also presented significant activity against L. guyanensis and L. braziliensis (Costa et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The alkaloid fraction from the barks of the trunk of U. guatterioides, (IC50 2.79 μg/mL) also showed significant activity, that can be attributed to the oxaporphine alkaloids liriodenina (3) and lisycamine (4) (Silva et al, 2012a), which showed good leishmanicidal activity (Waechter et al, 1999) when evaluated against promastigotes form of L. major and L. donovani. Liriodenine also presented significant activity against L. guyanensis and L. braziliensis (Costa et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that this alkaloid has significant leishmanicidal activity against promastigotes of L. braziliensis and L. amazonensis (Queiroz et al, 1996). The observation of the high activity of the alkaloid fraction of the leaves (IC50 1.90 μg/mL) may also be related to the presence of a majority aporphine alkaloid asimilobine (2) (Silva et al, 2012a), which recently was related as an anti-leishmanial compound (Mollataghi et al, 2012).…”
Section: In Vitro Evaluation Of the Leishmanicidal Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…Besides its attractive biological properties, the fast recognition and dereplication of this class in complex matrices by mass spectrometry (MS) has accelerated the research for new compounds . This favorable situation is possible due to the advances on the gas‐phase chemistry of aporphines through key fragmentation recognition via collision‐induced dissociation (CID) experiments .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Bocageopsis and Onychopetalum comprise few species, four and two, respectively (B. mattogrossensis, B. canescens, B. multiflora and B. pleiosperma, O. amazonicum and O. periquino) (Maas et al, 2007). Unonopsis is also the most explored from the chemical and biological viewpoints (Siqueira et al, 1998;Waechter et al, 1999;Silva et al, 2012bSilva et al, ,c, 2014. The chemical information regarding the Bocageopsis and Onychopetalum genera is still limited, being focused directed to the study of the essential oils and alkaloid compositions (Almeida et al, 1976;Oliveira et al, 2014;Soares et al, 2015).…”
Section: Introductionmentioning
confidence: 99%